1990
DOI: 10.1111/j.1365-2303.1990.tb00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of salivary gland lesions: advantages and pitfalls

Abstract: Fine needle aspiration cytology (FNAC) was performed on 52 patients with salivary gland lesions. A definitive cytodiagnosis was possible in 45 cases: a sensitivity of 89% and a specificity of 94% was achieved. The pitfalls of FNAC of salivary gland lesions are reflected by the false positive and false negative rates which were 4%. Errors of cytodiagnosis are due to the morphological variability of these tumours which make sampling and interpretation difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 14 publications
3
46
0
Order By: Relevance
“…This had occurred because one case of MEC was misdiagnosed as WT. The false positive rate has been reported to be low ( 0-10%) [2,15,16]. In our series, the false positive rate was 4.8 % and this was due to one case of Warthin's tumour, with extensive squamous metaplsia being diagnosed as MEC on FNAC.…”
Section: Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…This had occurred because one case of MEC was misdiagnosed as WT. The false positive rate has been reported to be low ( 0-10%) [2,15,16]. In our series, the false positive rate was 4.8 % and this was due to one case of Warthin's tumour, with extensive squamous metaplsia being diagnosed as MEC on FNAC.…”
Section: Methodsmentioning
confidence: 72%
“…Squamous cells and mucinous cells were interpreted as oncocytic cells and cyst discussiOn FNAC is a technique which is commonly used for the evaluation of both neoplastic and non neoplastic lesions which occur salivary gland [5][6][7]. The parotid gland was the commonly studied gland, followed by submandibular gland, a finding which has been well described in the literature [1][2][3][4][5][6][7][8][9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In cases of malignancy like carcinoma ex pleomorphic adenoma chances of false negative are there as heterogenecity plays an important role in these tumours. 10 Studies done in past also reveal good sensitivity in cases of metastatic lesions as metastatic cells can easily be identified as compared to their other cell variants 11 . Various studies done in past have reported a diagnostic accuracy of 86-98% for cytological diagnosis of salivary gland neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of FNAC from the salivary glands is, however, a difficult cytopathological technique with many problems and pitfalls.9 10 Although some of these are similar to those encountered in the interpretation of histological material" and are due to the varied and heterogeneous nature of salivary gland neoplasia, other dilemmas are inherent to FNAC -namely, uncertainty as to the site and tissues actually aspirated, minimal material, and the lack of architectural pattern in smears compared with histological sections.…”
Section: Introductionmentioning
confidence: 99%